PENGEMBANGAN MEDIA PEMBELAJARAN IPA DENGAN ANIMASI MACROMEDIA FLASH BERBASIS MODEL PENGAJARAN LANGSUNG (DIRECT INSTRUCTION) DI SEKOLAH DASAR - Naniek Kusumawati (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2015)
This research is the development of instructional media developed macromediaflash animation-based teaching model directly in SDN Mangkujayan II Ponorogo.Based on the research got enthusiastic excellent student this is evidenced by theresults of the data questionnaire responses following students on learning to usemedia such as macromedia flash animation, developed the data obtained by 36students (100%) expressed interest. Data questionnaire responses of students tothe language used in textbooks and media animation data obtained by 32 students(88.9%) expressed understandable and 4 students (11.1%) said it was difficult tounderstand. Data questionnaire responses of students to the illustrations intextbooks and media animation data obtained by 35 students (97.2%) expresseddelight and 1 student (2.7%) were not happy. Mastery of student learningoutcomes after the use of instructional media macromedia flash animation-basedteaching model directly based on analysis of data on student learning outcomesresults obtained by 28 students completed the individual, the individual is notfinished 8 students from 36 students who take the post-test. Mastery of cognitivelearning outcomes for students in classical 77.78%. This means that students ofclass V have achieved mastery of learning outcomes are classical.